Epizootic ulcerative syndrom (EUS) ion fishes of small-scale farmer's ponds in Bogra district of Bangladesh (University Journal of Zoology, Rajshahi University, 2007)
Key words: Epizootic ulcerative syndrom; small-scale farmer's ponds; low-cost treatment measure Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 11-18